The Analysis of Needs on Learning Materials in Context-Based Reading Mandarin Languages and Culture - Febi Nur Biduri; Yumna Rasyid; Emzir Emzir (JETL (Journal of Education, Teaching and Learning), 2018)
A research and development of teaching materials will focus on the development of the textbook that suit the needs of students, lecturers, and also the majors. The knowledge of culture and literature that has been studied in Chinese Language and Culture study program of Darma Persada University is not maximum and suitable for the students’ needs. So to adjust to the needs of these students, the making of teaching materials in this study will use the contextual based theme of Chinese literature and culture. The literature and cultural themes used in this study consists different types of traditional Chinese folklore. The methodology used in this study refers to Hutchinson and Waters theory that includes the analysis of the needs of students and teachers. The data collections are conducted using questionnaire in the 5th of Chinese Language and Culture Faculty of Darma Persada University which consist of 18 students and 3 lecturers in reading class. The data analysis used in this study is quantitative. This research resulted that the use of appropriate teaching materials and in accordance with the needs of students will result in more effective learning, better learning outcomes, and a positive response on student attitudes. The material for reading the context-based Mandarin literary works and culture resulting from this development research has also encouraged the students to be more active during the teaching and learning process.